Challenges of teaching multilingual students in tertiary education - Huszti Ilona; Lechner Ilona; Густі Ілона; Лехнер Ілона; Ilona Lekhner (H.S. Skovoroda Kharkiv National Pedagogical University, 2025)
Abstract. This study investigates the challenges encountered by teachers in educating multilingual students at the Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education in Ukraine. The college serves a diverse student population, including native Ukrainian speakers, Hungarian speakers, and others, creating a complex and dynamic multilingual learning environment. This research aims to understand the specific challenges faced by teachers in navigating this linguistic diversity to support all students' academic success. Methodology: The research employed a mixed-methods approach. Document analysis was conducted to examine the college's institutional language policies and their implications for teaching and learning. This included an analysis of official documents, such as the college charter and curriculum guidelines. Concurrently, observational data was collected from multilingual classrooms to understand real-time language practices. Results: The findings reveal several key challenges. Firstly, addressing varying levels of proficiency in Ukrainian, Hungarian, and English within the same classroom presents significant pedagogical demands. Providing individualized support, including extra tutoring and language support services, was also identified as crucial for ensuring all students can effectively engage with the learning material. Secondly, the effective use of intermediary languages, such as English, in facilitating instruction across different language backgrounds proved to be a crucial consideration. Conclusions: The study underscores the complexities of teaching in a multilingual environment. It highlights the importance of teacher training and professional development in areas such as multilingual pedagogy, intercultural communication, and the development and utilization of appropriate language learning resources. The findings of this study offer valuable insights for educators and policymakers in multilingual contexts, emphasizing the need for flexible and inclusive approaches to teaching and learning that address the unique linguistic and cultural needs of all students.

Резюме. У статті досліджено проблеми, з якими стикаються викладачі під час навчання багатомовних студентів у Закарпатському угорському інституті ім. Ференца Ракоці II. Інститут навчає студентів різної національності, включаючи носіїв української, угорської та інших мов і створюючи складне та динамічне багатомовне навчальне середовище. Метою дослідження є з’ясування конкретних проблем, з якими стикаються викладачі в умовах цього мовного різномаїття, щоб підтримати успішність навчання студентів. Методологія: У дослідженні застосовується змішаний метод. Було проведено дослідження нормативно-правової документації якою регулюється мовна політика закладу вищої освіти та процес навчання та викладання. Це включало аналіз офіційних документів, таких як статут інституту та навчальні програми. Водночас був проведений збір і аналіз даних про багатомовні аудиторії з метою розуміння мовного становища у реальному часі. Результати: За результатами дослідження виявлено кілька ключових проблем. По-перше, врахування різного рівня володіння українською, угорською та англійською мовами в одній групі вимагає специфічні педагогічні підходи. Було визначено, що надання індивідуальної підтримки та мовні курси, також є важливими для забезпечення ефективної успішності студентів у опануванні навчального матеріалу. По-друге, для полегшення навчання в різних мовних середовищах важливим фактором є ефективне використання мови-посередника, як наприклад, англійської. Висновки: Наголошено на складності викладання в багатомовному середовищі, на важливості підготовки вчителів та їх професійного розвитку в таких галузях, як багатомовна педагогіка, міжкультурна комунікація та розробка і використання відповідних навчальних методів. Результати дослідження дають цінні знання для педагогів, які працюють у багатомовному середовищі, підкреслюючи необхідність гнучких та інклюзивних підходів до навчання та викладання, які враховують унікальні мовні та культурні потреби студентів.
Виклики у процесі навчання багатомовних здобувачів у системі вищої освіти
Редакційна колегія: https://educationalchallenges.org.ua/index.php/education_challenges/about/editorialTeam Зміст: https://educationalchallenges.org.ua/index.php/education_challenges/issue/view/15
Keywords: language courses; language use inside and outside the classroom; learning management system; multilingual context; tertiary education; Transcarpathia; багатомовний контекст; використання мови в аудиторії та поза нею; вища освіта; Закарпаття; мовні курси; система управління навчанням